Staff of Officials of the Eastern Palace in Ancient China (Zien Journal of Social Sciences and Humanities, 2022)
The system of conferring aristocratic titles and honorary titles by the monarch in ancient China was a feudal hierarchical system that monarchs of different dynasties established to consolidate their power and regulate relations within the ruling class. The title and rank indicated the position of an aristocrat or dignitary. They were divided by ranks and showed the place that their owner occupied in society. Some titles were hereditary and could be inherited. Those who were assigned the title, as a rule, received land plots or the corresponding amount of material goods. The system of conferring titles and titles has evolved in China over several thousand years, with significant changes. The main source for this article was the materials of the Encyclopedia of China Encyclopedia